Pengaruh Project Based e-Learning Terhadap Keterampilan Berpikir Kritis dan Prestasi Belajar IPAS Peserta Didik Kelas X - R.A. Aktafianto; I.M. Yudana; I.P.W. Ariawan (Pascasarjana Universitas Pendidikan Ganesha, 2023)
The purpose of this study was to determine the effect of the project-based e-Learning learning model on critical thinking skills and science achievement. This research has a quasi-experimental design. The population of this study was class X SMK Negeri 1 Tembuku for the 2022–2023 academic year, consisting of 10 classes (259 students). The research sample was taken using the random sampling technique; two classes were determined as samples and divided into two groups, namely the experimental group and the control group. Critical thinking skills data was collected with an essay test, and in science, learning achievement data was collected with an expanded multiple-choice test. Data analysis used the one-way MANCOVA statistical test with a significance level of 5% and continued with the LSD test. The results showed that (1) There are differences in critical thinking skills and learning achievement in science between students who learned with the PjBeL model and students who learned with the DEL model. (2) There are differences in critical thinking skills between students who learned with the PjBeL model and students learning with the DEL model. (3) There are differences in science learning achievement between students who learned with the PjBeL model and students learning with the DEL model. Based on the results of the study, it can be concluded that the PjBeL model influences students' critical thinking skills and learning achievement in science in Class X SMKN 1 Tembuku.